Defect and Interface Engineering on Two‐Dimensional Nanosheets for the Photocatalytic Nitrogen Reduction Reaction. Issue 12 (4th November 2020) - Zhao, Wenjun; Liu, Baojun; Qin, Jiangzhou; Ke, Jun; Yu, Lanlan; Hu, Xia
Abstract: Reducing dinitrogen (N2 ) to ammonia (NH3 ) under mild conditions is a very significant nitrogen cyclic process, which plays a vital role in agricultural, biological and industrial fields. The Haber‐Bosch process as a current mainstream way of N2 fixation has particularly high energy consumption, occupying about 1 % of the world energy production. In contrast, the photocatalytic N2 reduction reaction provides a green route almost without energy consumption and environmental pollution. However, there are many challenges that needs to be solved urgently, such as, for example, low quantum yield, inefficient N2 adsorption and activation and an unclear N2 fixation mechanism. Nowadays, tactics for improving the catalytic performance mainly focus on producing more active sites via defect or interface engineering. Generally, two‐dimensional materials with defect or interface engineering can not only accelerate photon‐exciton interactions, but also enhance sufficient N2 binding, activation and hydrogenation. In this Minireview, we will first summarize the principles of photocatalytic N2 fixation, and then discuss progress in the development two‐dimensional (2D) materials with defect and interface engineering for photocatalytic N2 fixation. Finally, we describe ammonia detection methods and recent important developments and challenges in this field. Abstract : Defect and interface engineering in two‐dimensional photocatalysts for enhancing the efficiency of the photocatalytic nitrogen reduction reaction under ambient conditions were reviewed.